Intersex in Italy: At the Source of the Complexity? - Lorenzetti, Anna (The Age of Human Rights Journal, 2022)
Focusing on the Italian legal scenario, the paper examines medical practices that impose cosmetic surgeries on intersex children. Carried out with the aim of adjusting their genitalia to a perfect male or female body, these practices infringe upon the fundamental rights of the children subjected to them and demand new ways of protection. The paper explores the legal approaches that could be adopted to challenge them and to ensure the protection of children’s rights.